Structural and Diffusion MRI Analyses With Histological Observations in Patients With Lissencephaly - Vasung, Lana; Rezayev, Arthur; Yun, Hyuk Jin; Song, Jae W.; van der Kouwe, Andre; Stewart, Natalie; Palani, Arthi; Shiohama, Tadashi; Chouinard-Decorte, Francois; Levman, Jacob; Takahashi, Emi (Frontiers in Cell and Developmental Biology, 2019)
The development of cortical convolutions, gyri and sulci, is a complex process that takes place during prenatal development. Lissencephaly, a rare genetic condition characterized by the lack of cortical convolutions, offers a model to look into biological processes that lead to the development of convolutions. Retrospective, qualitative, and quantitative analyses of structural magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI) were performed in patients with lissencephaly (N = 10) and age-/sex-matched controls (N = 10). In order to identify microstructural correlates of structural MRI and DTI findings, postmortem brains of patients with lissencephaly (N = 4) and age-matched controls (N = 4) were also examined with histology. Patients with lissencephaly had significantly smaller gyrification index and volumes of hemispheric white and gray matter, compared to the age-/sex-matched control group. However, there was no significant difference between groups in the subcortical gray matter volumes. Although the majority of patients with lissencephaly had a preserved normal-like appearance of major fissures and primary sulci, the spatial distribution of agyric cortical regions was different in patients with lissencephaly-1 (LIS1) and doublecortin (DCX) mutations. Lastly, in patients with lissencephaly, the spatiotemporal distribution of projection pathways was preserved while short- to medium-range cortico-cortical pathways were absent or fewer in number. Our results indicate that in the patients with lissencephaly cortical system is affected more than the subcortical one.